2016
DOI: 10.1111/ina.12330
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of the fungal fraction released from various preloaded fibrous filters during a simulated ventilation restart

Abstract: This study aimed to demonstrate that particles, especially those associated with fungi, could be released from fibrous filters used in the air-handling unit (AHU) of heating, ventilation and air-conditioning (HVAC) systems during ventilation restarts. Quantification of the water retention capacity and SEM pictures of the filters was used to show the potential for fungal proliferation in unused or preloaded filters. Five fibrous filters with various particle collection efficiencies were studied: classes G4, M5,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Several studies have shown that stress-resistant spores can remain viable over a prolonged period of time and even grow in the filter media ( Forthomme et al, 2014 ). The spores collected on filters can be re-aerosolized during replacement or maintenance ( Morisseau et al, 2017 ), thereby posing a health risk. In order to overcome this disadvantage of pleated fibrous filter, UV+Filter system is developed for indoor ventilation systems.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown that stress-resistant spores can remain viable over a prolonged period of time and even grow in the filter media ( Forthomme et al, 2014 ). The spores collected on filters can be re-aerosolized during replacement or maintenance ( Morisseau et al, 2017 ), thereby posing a health risk. In order to overcome this disadvantage of pleated fibrous filter, UV+Filter system is developed for indoor ventilation systems.…”
Section: Resultsmentioning
confidence: 99%
“…The risk of Fibrous-filter is re-aerosolization of deposited particles (e.g. spore) during replacement or maintenance ( Morisseau et al, 2017 ). Professional property service and system maintenance were needed for Fibrous-filter users.…”
Section: Discussionmentioning
confidence: 99%
“…The microbial growth onto fibrous filters is influenced by the air humidity [8], but even more by the water retention capacity of the filters [8,10]. Water is sorbed by the fibers of the filter and/or by the particles collected by the filter according to the hydrophilic characteristics of the fibers and the particles.…”
Section: Water Retention Capacitymentioning
confidence: 99%
“…Microbial growth onto HVAC filters was observed in the literature under laboratory conditions [7][8][9][10], and also in real conditions [11,12], with possible degradation of the Processes 2021, 9, 1528 2 of 13 microbial indoor air quality. To address this issue, innovative air filters with photocatalytic properties [13] or containing antimicrobial treatments are designed to be implemented in HVAC systems, or in portable room air cleaners or automobiles.…”
Section: Introductionmentioning
confidence: 99%
“…Filtration [2] and electrostatic precipitation [3] belong to the latter category. Microbes trapped inside filters can multiply in situ [4,5,6,7,8]; such filters are detrimental to indoor air quality and hazardous during their disposal. They also offer high flow resistance which translates to high operating power consumption [9,10].…”
Section: Introductionmentioning
confidence: 99%